In Silico Biological Profile Prediction of Some Selectively Synthesized Acyl Rhamnopyranosides - Chowdhury, S. A.; Bhattacharjee, S. C. (Journal of Scientific Research, 2021)
Over the past several decades significant biological activities including brains protective and antimicrobial activities have made sugar esters (SEs) as a topic of great interest. In this context, unimolar 3-chlorobenzoylation of methyl α-L-rhamnopyranoside (4) using dibutyltin oxide method regioselectively furnished only the 3-O-substitution product 5 in excellent yield. The reaction proceeded via the formation of a cyclic 2,3-O-dibutylstannylene intermediate where equatorial hydroxyl group is activated by the tin atom leading to the formation of product 5 only. To get biologically important rhamnopyranoside esters chlorobenzoate 5 was further converted into three newer 2,4-di-O-acyl products 6-9 with other acylating agents using direct acylation method. Prediction of activity spectra for substances (PASS) indicated that these rhamnopyranoside esters have many promising biological profiles including CYP2H substrate, membrane permeability inhibitor and better antifungal activities. Additionally, ADMET and drug likeness properties of SEs 5-8 were predicted and discussed.